Rancang Bangun Sistem Informasi Pemasaran Pada PT Orange Point Arsitek Daerah Condet Berbasis Neatbeans 8.0 - Dona Katarina; Muslihatul Hidayah (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of the research is to facilitate the design of a Java-based Marketing Information System that can help management in determining its business strategy and solving problems related to marketing. The research methods used are grounded research and observation methods. The grounded research method is a research method that is based on facts and uses comparative analysis with the aim of conducting empirical generalizations, establishing concepts, proving theories, developing theories, collecting and analyzing data at the same time. While the observation method is a method of collecting data that is carried out systematically and deliberately through observation and recording and symptoms of the object being studied directly in the field